Analisis Penentuan Suku Bunga Dasar Kredit Ritel ( Studi Empiris pada Bank BUMN di Indonesia Periode Oktober 2011 – Maret 2013 ) - Brando Pratenta Ginting; Syarief Fauzie (Departemen Ekonomi Pembangunan USU, 2014)
This research was conducted to determine the factors that influencing the determination of the retail prime lending rate on government bank in Indonesia. The main purpose of this research is to analyze the influence of BI rate and BOPO for the determination of the retail prime lending rate. The data used in this research is a secondary data which the object of this study is the government bank by using the Financial Statements of the period October 2011 - March 2013.The data in this study is the type of panel data that analyzed using panel data regression of the fixed effect model (FEM) which was considered suitable in this research because the model has a different intercept equations or constant on each individual. Before analyzing the data, first tested for normality and test redundant fixed effect to determine whether the data that normally distributed and used to determine the suitability of the fixed effect model for this research.Further processing of the data were performed using the Eviews 6.The results showed that simultaneously the BI rate and BOPO variables with significant impact on the retail prime lending rate at 95% confidence level. In addition, from the values shown by the coefficient of determination shows that the BI rate and ROA variables are able to explain the variable the re0tail prime lending rate amounted to 97,7%.Key words : BI Rate, BOPO, Prime Lending Rate